Conquering character : the characterization of Joshua in Joshua 1-11 - Hall, Sarah Lebhar (Library of Hebrew Bible/Old Testament studies ;, 2010)
While recent Old Testament scholarship has seen a steady rise in the prominence of narrative approaches to the text, little such work has been done on the book of Joshua. This book offers a narrative treatment of the conquest accounts, with specific attention given to the characterization of Joshua. The method employed is eclectic, including poetic analysis, structural study, delimitation criticism, comparative literary analysis, and intertextual reading. Joshua's characterization has received inadequate scholarly attention to date, largely because he is seen as a pale character, a mere stereotype in the biblical history. This two-dimensional reading often leads to the conclusion that Joshua is meant to represent another character in the history. But this approach neglects the many aspects of Joshua's character that are unique, and does not address the text's presentation of his flaws. On the other hand, some scholars have recently suggested that Joshua's character is significantly flawed. This reading is similarly untenable, as those features of Joshua's leadership that it portrays as faulty are in fact condoned, not condemned, by the text itself. Close examination of the conquest narratives suggests that Joshua's character is both complex and reliable. To the degree that Joshua functions as a paradigm in the subsequent histories, this paradigm must be conceived more broadly than it has been in the past. He is not merely a royal, prophetic, or priestly figure, but exercises, and often exemplifies, the many different types of leadership that feature in the former prophets.